2016
DOI: 10.1111/rda.12721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Silymarin and Caproic Acid on Storage of Ram Semen in Liquid Form

Abstract: Two experiments were designed to evaluate the effect of silymarin on stored spermatozoa using four rams. In experiment 1, silymarin was evaluated as a supplement for Tris-glucose extender. Semen samples (n = 20) were diluted with extender containing 0, 50, 100, 150 and 200 μg/ml silymarin and incubated at 5°C for 72 h. Membrane integrity, acrosome integrity, sperm viability and motility were evaluated at 72 h. Concentration of malondialdehyde (MDA) was determined after 48 h. Membrane integrity was higher in 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…SMN had protective effects on human sperm against oxidative stress induced by environmental pollutants (Aghashahi et al, 2020). Roostaei‐Ali proved that SMN could improve ram sperm quality preserved at 5°C (Roostaei‐Ali Mehr & Parisoush, 2016). Given these findings, we suggested that SMN had positive effects on cryopreserved sperm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SMN had protective effects on human sperm against oxidative stress induced by environmental pollutants (Aghashahi et al, 2020). Roostaei‐Ali proved that SMN could improve ram sperm quality preserved at 5°C (Roostaei‐Ali Mehr & Parisoush, 2016). Given these findings, we suggested that SMN had positive effects on cryopreserved sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SMN was able to overcome the adverse effects of sperm under oxidative stress conditions. Reportedly, the supplementation of SMN improved goat sperm quality by its antioxidant properties (Roostaei‐Ali Mehr & Parisoush, 2016). In the present study, we found that the addition of SMN could dramatically increase T‐AOC activity, in the meanwhile, decrease the tROS and MDA content of post‐thaw spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…Silymarin is an efficient antioxidant, scavenging free radicals and protecting cells against LPO [103]. It has been reported that the addition of sylimarin (100 µg/L) to a Tris-glucose extender improves motility, membrane and acrosome integrity, and reduces LPO as indicated by the MDA concentration during liquid storage of ram semen at 5˚C up to 72 h [97].…”
Section: Plant Extractsmentioning
confidence: 99%
“…Silymarin exerts its antioxidant properties by scavenging free radicals, increasing antioxidant defence enzymes levels and decreasing lipid peroxidation levels (Fraschini, Demartini, & Esposti, 2002). In this context, several in vitro and in vivo studies demonstrated the protective effects of silymarin on sperm parameters, varicocele‐induced lesions and prostate cancer (Eskandari & Momeni, 2016a; Moshtaghion, Malekinejad, Razi, & Shafie‐Irannejad, 2013; Roostaei‐Ali Mehr & Parisoush, 2016).…”
Section: Introductionmentioning
confidence: 99%